2007
DOI: 10.3758/bf03196807
|View full text |Cite
|
Sign up to set email alerts
|

Models of covariation-based causal judgment: A review and synthesis

Abstract: Over the past 25 or so years, many researchers have sought to characterize the mechanisms by which people form causal beliefs from covariation information. This can be seen as a special case of the fundamental problem of associative learning (in a broad sense)-namely, the problem of describing how learned beliefs relate to the environmental contingencies on which they are based. Causal beliefs are influenced by a range of factors such as the temporal (Shanks, Pearson, & Dickinson, 1989; see also Buehner & May,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
141
3
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(161 citation statements)
references
References 56 publications
8
141
3
9
Order By: Relevance
“…The usual finding is that A B C D (Anderson & Sheu, 1995;Levin, Wasserman, & Kao, 1993;Mandel & Lehman, 1998;Wasserman, Dorner, & Kao, 1990;Wasserman, Kao, Van Hamme, Katagiri, & Young, 1996;White, 2003a). White (2004) set weights in accordance with the findings of previous research and found that a model with those weights, termed wpCI (weighted proportion of confirming instances), was a better predictor of causal judgment than was the original pCI rule (see also Perales & Shanks, 2007).…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The usual finding is that A B C D (Anderson & Sheu, 1995;Levin, Wasserman, & Kao, 1993;Mandel & Lehman, 1998;Wasserman, Dorner, & Kao, 1990;Wasserman, Kao, Van Hamme, Katagiri, & Young, 1996;White, 2003a). White (2004) set weights in accordance with the findings of previous research and found that a model with those weights, termed wpCI (weighted proportion of confirming instances), was a better predictor of causal judgment than was the original pCI rule (see also Perales & Shanks, 2007).…”
supporting
confidence: 77%
“…To ameliorate predicted sample size effects, the predicted values in Tables 1-3 were generated by using a power transformation of the form j sign(support) abs(support) k , as recommended by Griffiths and Tenenbaum (2005). I followed the procedure used by Perales and Shanks (2007), searching k in intervals of 0.05 to find the maximum fit between support and judgments. Across the data sets used in Experiments 1 and 2, the best fit was found at k .35; those are the values reported herein.…”
Section: Assessment Of Other Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Allan & Jenkins, 1983;Matute, Yarritu, & Vadillo, 2010;Perales, Catena, Shanks, & González, 2005;Wasserman et al, 1996). In spite of the formal parallelism between both density effects, the available evidence strongly suggests that the cue-density effect is smaller and less robust than the outcome-density effect (e.g., Hannah & Beneteau, 2009;Perales & Shanks, 2007).…”
mentioning
confidence: 93%
“…By a recent count, over 40 algorithmic models of causal learning have been proposed in the literature (Hattori & Oaksford, 2007), almost all of which are nonnormative heuristics. Perales and Shanks (2007) compiled a metaanalysis of data from 114 conditions, taken from 17 experiments from 10 studies conducted in multiple labs, varying a variety of quantitative and qualitative parameters related to causal learning. Lu et al (2008) showed that the parameter-free Bayesian power PC model provides the best quantitative fit of any model that has been applied to the data in this meta-analysis (r ϭ .96).…”
Section: Bayesian Theory Of Inference Guided By Causal Modelsmentioning
confidence: 99%